Status Perubahan Akad Wadi’ah Yad Al-Amanah menjadi Wadi’ah Yad Adh-Dhamanah Pada Bank Syariah - Nuraheni Fitroh R. Syarkarna; Wahyu Duta Ronaldo; Fahrul Hidayat (Universitas Muhammadiyah Ponorogo, 2021)
The change in the ‘aqad (contract) that occurs in the wadi’ah contract includes the contract that fulfills the nature of the built which is not binding so that one of the parties can cancel the first contract and can make a new contract again. The reasons for the cancellation of the wadi’ah contract are one of the parties who felt disappointed. This change in the wadi’ah contract is also called the nafidz gair lazim contract. it is called that because it can be implemented as a result of the law in the sense that each party or one of them has khiyar rights or indeed because the original nature of the contract is not binding full (gair lazim) so that the contract can change when there is a problem in carrying out the contract.